La rotación de cultivos en el valle cálido del Magdalena: Un enfoque conservacionista de alto rendimiento (1996)
Experiments were carried out during five years at the "Nataima" Research Center, located at 431 ni.a.s.l. with average temperature of 28°C and annual rainfall of 1274 mm, on a soil classified as Arenic Haplustaif, to evaluate different crops rotation based on rice and sorghum; the combinations used were as follows: rice-rice (R-R), rice-soybean (R-Sy), rice-crotataria-sorghum (R-C-S), sorghum-sorghum (S-S), sorghum-soybean (S-Sy) and cotton-sorghum (Al-S). Simultaneously it was evaluated the response to four nitrogen levels, which allowed to find out yield functions and the optimun economical. The rotations S-Sy, R-Sy and Al-S have been the best qualified from an environmental perspective. Sorghum-soybean rotation presents increases in yield compared with expected values which allows to think that it is a truely sustainable rotation. This rotation also had an excelent profitability and for that reason is considered the best option within the goals of this work.